2018
DOI: 10.1007/jhep09(2018)013
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and action for warped AdS black holes

Abstract: The Complexity=Action conjecture is studied for black holes in Warped AdS 3 space, realized as solutions of Einstein gravity plus matter. The time dependence of the action of the Wheeler-DeWitt patch is investigated, both for the non-rotating and the rotating case. The asymptotic growth rate is found to be equal to the Hawking temperature times the Bekenstein-Hawking entropy; this is in agreement with a previous calculation done using the Complexity=Volume conjecture. arXiv:1806.06216v1 [hep-th]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 75 publications
(113 reference statements)
1
25
0
Order By: Relevance
“…20, we explore the linear regime and saturation of entanglement evolution on a circle for N = 2001 and β = 0.01L, for masses ranging from mL = 0.001 to 100, where we increase 40 We would like to thank Pasquale Calabrese for pointing this out to us. 41 In fact, we fix the values of the dimensionless parameters m L and β/L. the mass by a factor of 10 in each step.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…20, we explore the linear regime and saturation of entanglement evolution on a circle for N = 2001 and β = 0.01L, for masses ranging from mL = 0.001 to 100, where we increase 40 We would like to thank Pasquale Calabrese for pointing this out to us. 41 In fact, we fix the values of the dimensionless parameters m L and β/L. the mass by a factor of 10 in each step.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The first estimates of the late time holographic complexity growth rate for rotating AdS black holes appeared in [7,16], before a complete understanding of how to treat the action contributions of null boundaries was developed in [9]. For lower dimensional black holes, this computation was revisited in [51,52]. They studied the CV and CA growth rate in three dimensional warped AdS black holes, which include rotating BTZ as a subcase.…”
Section: Introductionmentioning
confidence: 99%
“…Then, for the case of warped geometries, the results of path-integral complexity could be compared with those of holographic calculations using the complexity = action or complexity = volume [24][25][26].…”
Section: Building Quantum Circuits From Kac-moody Symmetry Gatesmentioning
confidence: 99%
“…Also, in this setup, it has been shown that the entropy of a thermal state matches with the entropy of a warped BTZ black hole. In addition, the calculations for entanglement entropy and even subregion complexity have already been done for such solutions [24][25][26]. Furthermore, interesting relationships between WCFTs which show semi-local properties and other models such as SYK with complex fermions which has maximal chaos have been found in [27].…”
Section: Introductionmentioning
confidence: 99%